Reassesing Women’s Humanity: A Comparative Study of Islamic Teaching and Societal Perceptions - Mohsen Sallam, Abdulnaser Sultan; b Syed Abdul Rahman, Syed Mohammad Hilmi; Harun, Muhammad Safwan; Samudin, Siti Aisyah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The societal perspective on women encompasses a wide array of beliefs, attitudes, and practices that influence their roles and status within various cultures. These issues highlight the gap between Islamic teachings and societal practices, underscoring the need for a deeper understanding of Islamic principles regarding women’s rights and the importance of addressing cultural biases that hinder women’s progress. Hence, this article explores the concept of women’s humanity within the context of Islam and society. It addresses the historical and contemporary treatment of women, highlighting the frequent justification of various forms of oppression and subjugation in the name of religion. The aim is to clarify the Islamic view of women and compare it with societal perceptions, examining the reasons behind these views and offering a critique. Through critically examining relevant issues, the study reveals the apparent differences between the Islamic perspective and societal views on women. It emphasizes the need to reassess women’s roles through the overarching objectives of Shari‘ah (maqasid al-shari‘ah), asserting that recognizing women’s humanity is essential for the renewal of Islamic thought and the reform of societal realities. Therefore, women’s issues in Islamic sciences (shari’ah) must be re-examined using a framework based on core Islamic sources, namely the Qur’an and Sunnah.